The Impact of Cash Management and Fund Revenue on the Financial Performance of Gereja Masehi Advent Hari Ketujuh (GMAHK) - Busdan, Jennet Juliana; Sumanti, Elvis Ronald (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to examine the effect of cash management and public support on the financial performance of nonprofit religious organizations, specifically the Gereja Masehi Advent Hari Ketujuh (GMAHK) in Eastern Indonesia. The study tests whether liquidity and external funding influence financial sustainability and financial independence. Research Method: This research employs a quantitative design using multiple linear regression with AR(1) autocorrelation correction. The study uses 115 financial statement observations from GMAHK for the period 2013–2025. The dependent variables are the operational reserve ratio and the self-reliance ratio, while the independent variables are the cash ratio and the public support ratio. Results and Discussion: The findings show that cash management does not significantly affect either operational reserves or financial independence. In contrast, public support has a significant but different effect on the two indicators: it negatively affects operational reserves and positively affects financial independence. This indicates that external funding is more likely to be used for operational needs than for reserve accumulation. Implications: The findings suggest that nonprofit religious organizations need balanced funding strategies that support both program implementation and reserve building to strengthen long-term financial sustainability. Originality: This study contributes by providing empirical evidence on financial performance determinants in nonprofit religious organizations in Eastern Indonesia.